Effect of Diode Laser on Antibiotic Sensitivity and Biofilm Formation by Streptococcus Spp. Isolated from Dental Caries - Saja Ali Shareef; Aya Saadoon Dawood; Reem Naeem Al-Azzawi (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Streptococci from dental caries were isolated and identified during this study. The samples were collected from different Dental clinics in Baghdad. Cultural, morphological and biochemical test were used to identify all isolates, the results showed that all isolates belong to Streptococcus spp The susceptibility of 10 isolates toward 10 of common antibiotics, was tested, results showed that several isolates of Streptococcus spp. Isolated from dental caries were resistant to most of the antibiotics used. The percentages of resistance were 100% of isolates resistant to cephalothin and cefixime, 90% of isolates resistant to ampicillin, naldixic acid and erythromycin, 70% of isolates resistant to bacitracin and tetracycline, while 100% of isolates sensitive to gentamycin, ciprofloxacin and chloramphenicol. The susceptibility to antibiotics of two isolates after exposure to diode laser was increased toward chloramphenicol, tetracycline and naldixic acid. Two isolates showed increased susceptibility to chloramphenicol after I minute from exposure to diode laser. Also two isolates showed increased susceptibility to naldixic acid after 3 minute from exposure to diode lases. The increasing susceptibility to tetracycline begin after 10 minute for second isolate, while first isolate showed increased susceptibility to tetracycline after 5 minute from exposure to diode laser. Also the diode laser affected on viability of bacteria that increased with increased time of exposure.